Neuro-Spike Communications with Multiple Synapses under Inter-Neuron Interference [Article] - Maham, Behrouz; Kizilirmak, Refik Caglar (Institute of Electrical and Electronics Engineers, 2018)
The nervous system is a complex intra-body communication system, called neuro-spike communications, for transferring vital information throughout the body. This system consists of unreliable neural components like axon and synapses. The nervous system can deal with the unreliability of its components by making use of multiple synapses. In this paper, we analyze the performance of neuro-synaptic channels consisting of multiple synapses. It is assumed that synaptic channels are subject to synaptic noise, random vesicle release, and inter-neuron interference. The optimal detection for two cases of multiple cooperative synapses and multiple interfering synapses is investigated. The closed-form expressions of the probability density function of variable quantal amplitude are derived that is used to calculate the probability of detection error.
https://ieeexplore.ieee.org/document/8409926
Keywords: nervous system; neuro-spike communications; axon and synapses; variable quantal amplitude